A study of correlation between golf shaft stiffness and swing speed - Shee, Soon Ngen. (2012)
Golf club fitting is the process of matching player characteristic with appropriate club specification which requires numerous amounts of trial and error. Loft, lie angle, shaft flexibility and club length are widely accepted as being the five fitting variables that affect game performance of an individual golfer adversely. Considerable argument surrounds the individual and combined dynamic effect of these variables during golf swing. This project mainly aims to examine the effect of driver of different shaft stiffness on certain game performance measures. Other than that, the objectives of this project included evaluation of key fitting parameter and investigation of relationship between the parameter and player physical characteristics. A laboratory based experimental approach was implemented in the study. A total of ten right handed male golfers were recruited to participate in this investigation. Personal information and physical characteristics were obtained from each subject and to be used in correlational study with shot performance variables. Measurements of ball launch parameter and elements of playability were obtained from TrackMan for each subject during swing of each of three experimental clubs.